The Phantom Root: Clinical Resolution of a Radiographic Illusion in the Maxillary Posterior Region - Mishra, Riya; Kiran, Pandey; Tandon, Sapna; Mehra, Hemant; Chauhan, Himanshu; Pandey, Priyanka (Journal of Neonatal Surgery, 2025)
Background:Anatomical variations in maxillary third molars often complicate radiographic interpretation, especially in edentulous regions. This can lead to diagnostic challenges and potential overtreatment due to misidentification of structures. Case Presentation:A 58-year-old male presented with intermittent pain in the upper right maxillary posterior region. Clinical examination revealed a grossly carious maxillary third molar and an absent second molar with no history of extraction. Periapical radiograph showed a radiopaque structure suggestive of a second molar root. Surgical exploration revealed that this image was due to an elongated, curved palatal root of the third molar mimicking the second molar root. No additional root structure was found. Discussion:The case illustrates how anatomical deviations in third molar root morphology, combined with limitations of 2D imaging, can create illusions leading to misdiagnosis. Radiographic overlap and the absence of adjacent teeth further complicate interpretation. Awareness of such possibilities and use of 3D imaging like CBCT can prevent diagnostic errors. Conclusion:Clinicians must maintain a high index of suspicion in cases of inconsistent clinical and radiographic findings. Knowledge of anatomical variations, corroborated with advanced imaging when needed, is essential to prevent unnecessary procedures.